Factor Structure of the FFM ATM: Antagonism, Emotional Stability, Impulsivity, and Agency. Issue 3 (4th May 2023) - Rose, Leigha; Crowe, Michael L.; Sharpe, Brinkley M.; Van Til, Kaela; Lynam, Donald R.; Miller, Joshua D.
Abstract: The Dark Triad (DT) refers to three socially aversive personality constructs: psychopathy, narcissism, and Machiavellianism. In response to concerns with existing self-report questionnaires measuring these constructs, we created the Five Factor Model Antagonistic Triad Measure (FFM ATM), which uses 46 items to assess multidimensional, faceted versions of the three DT constructs. The current pre-registered study used two large samples ( N s = 600 and 1, 247) to explore the structure of the FFM ATM using bass-ackward factor analyses. Participants completed the FFM ATM as well as measures of the five-factor model, aggression, antisocial behavior, and other criteria. A series of factor analyses identified four meaningful and replicable factors (i.e., Antagonism, Emotional Stability, Impulsivity, and Agency). The authors discuss the item composition of each of these factors, their relations to relevant criteria, and implications of conceptualizing the Antagonistic Triad as combinations of elemental traits (factors) as opposed to the multidimensional constructs of psychopathy, narcissism, and Machiavellianism.